2018
DOI: 10.3168/jds.2017-14190
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of exosomes derived from plasma of heifers with divergent genetic merit for fertility

Abstract: The current study evaluated exosomes isolated from plasma of heifers bred to have high or low fertility through developing extreme diversity in fertility breeding values, however, key animal traits (e.g., body weight, milk production, and percentage of North American genetics) remained similar between the 2 groups. The exosomes were isolated by a combined ultracentrifugation and size exclusion chromatography approach and characterized by their size distribution (nanoparticle tracking analysis), morphology (tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
(54 reference statements)
0
17
0
1
Order By: Relevance
“…Their interaction with the targeted cell can directly activate membrane receptors or alter the extracellular environment by releasing their contents into the targeted cell 19 . Circulating exosomes isolated from dairy cows may have potential as indicators of fertility status 20 , uterine diseases 21 , and metabolic diseases 22 , as they carry proteins that are unique to the state of the cow.…”
Section: Introductionmentioning
confidence: 99%
“…Their interaction with the targeted cell can directly activate membrane receptors or alter the extracellular environment by releasing their contents into the targeted cell 19 . Circulating exosomes isolated from dairy cows may have potential as indicators of fertility status 20 , uterine diseases 21 , and metabolic diseases 22 , as they carry proteins that are unique to the state of the cow.…”
Section: Introductionmentioning
confidence: 99%
“…This is because milk fat, protein, and lactose percentages are predicted from MIR spectra (De Marchi et al, 2014). Moreover, it also implies that MIR spectra contain other information related to the fertility status of the animal, which might be further elucidated using metabolomics (Phillips et al, 2018), proteomics (Koh et al, 2018), or genome-wide association studies (Wang and Bovenhuis, 2018;Benedet et al, 2019). In terms of a practical application, these results mean that MIR was of primary importance in prediction of fertility of dairy cows.…”
Section: Resultsmentioning
confidence: 98%
“…The choice of the characterization protocol relies on sample type, isolation method and the application of isolated exososmes. In the case of bovines, different exosomes-containing body fluids have been deeply analyzed, including colostrum and milk [ 78 , 79 , 80 , 81 , 82 ], serum and plasma [ 78 , 83 , 84 , 85 , 86 , 87 , 88 ], urine [ 78 , 89 ], and saliva [ 78 ].Through comparative studies of different bovine biological fluids, a recent study reported that plasma and milk collected from cows have a significantly higher abundance of EXO, in comparison to their urine and saliva [ 78 ].…”
Section: Characterization Of Exomentioning
confidence: 99%